Development of Computer-Based Instruction Based Learning Models in Electricity Transmission Engineering Lessons SMK Negeri 1 Precut Sei Tuan - Muhammad Iqbal Daulay; R. Mursid; Baharuddin Baharuddin (BIRCU, 2020)
One of the formal education pathways that prepare its graduates to have excellence in the world of work is Vocational High Schools (SMK). Current problems in SMK are generally related to limited equipment, low practice costs, and a learning environment that is not suitable for the world of work. Education is carried out to achieve human resources with the ability to think which is formulated as